2020
DOI: 10.1039/d0nr04127k
|View full text |Cite
|
Sign up to set email alerts
|

Self-healing on mismatched fractured composite surfaces of SiC with a diameter of 180 nm

Abstract: Self-healing is demonstrated by an in situ nanomechanical test on mismatched fractured amorphous and crystalline composite surfaces of SiC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Lu et al grew carbon nanotube films on stainless steel by plasma enhanced CVD for corrosion resistance enhancement, and they indicated that the corrosion current density of coated substrates can be slightly decreased (≈ 90%), as compared with bare one (Lu et al 2019). In addition, some studies on nanostructures shows that surface morphologies and nanostructures, consisting of nanoscale chips have a significant influence on the precision and performance of devices in semiconductor, optoelectronics and microelectronics industries (Zhang et al 2013(Zhang et al , 2012a(Zhang et al , 2012b(Zhang et al , 2020Han et al 2020;Cui et al 2019;Meng et al 2020;Liao et al 2020). However, although the direct formation of nanostructured carbon coatings on stainless steel using CVD has been reported, their porous nature cannot make best use of corrosion protection for bipolar plate applications (Baddour et al 2009;Taha et al 2019;Masarapu et al 2007;Chun et al 2005).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Lu et al grew carbon nanotube films on stainless steel by plasma enhanced CVD for corrosion resistance enhancement, and they indicated that the corrosion current density of coated substrates can be slightly decreased (≈ 90%), as compared with bare one (Lu et al 2019). In addition, some studies on nanostructures shows that surface morphologies and nanostructures, consisting of nanoscale chips have a significant influence on the precision and performance of devices in semiconductor, optoelectronics and microelectronics industries (Zhang et al 2013(Zhang et al , 2012a(Zhang et al , 2012b(Zhang et al , 2020Han et al 2020;Cui et al 2019;Meng et al 2020;Liao et al 2020). However, although the direct formation of nanostructured carbon coatings on stainless steel using CVD has been reported, their porous nature cannot make best use of corrosion protection for bipolar plate applications (Baddour et al 2009;Taha et al 2019;Masarapu et al 2007;Chun et al 2005).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…To address these challenges, low-dimensional materials produced by bottom-up methods have been taken advantage in NEMS resonators. Among many materials deemed suitable for NEMS resonators, 1D nanomaterials, such as silicon nanowires, [13,14] carbon nanotubes (CNT), [15][16][17][18] zinc oxide (ZnO) nanowires, [19][20][21][22] and silicon carbide (SiC) nanowires, [23][24][25] are promising candidates for realizing high-performance NEMS resonators because of its excellent mechanical properties; particularly high Young's modulus, small size and high volume ratio. Researchers have demonstrated suspended 1D nanomaterials as NEMS devices with potential applications as gas detection sensors, nano electronics, or quantum motion detectors.…”
Section: Introductionmentioning
confidence: 99%